Peter in early Christianity - Bond, Helen K.; Hurtado, Larry W. (William B. Eerdmans Publishing Company, 2015)
Long overshadowed by the apostle Paul, Peter has received increased scholarly attention of late. Building on that resurgence of interest, nineteen internationally prominent scholars of early Christian history examine and reassess the historical Peter and his significance in Christian texts from the first three centuries. Giving due attention to archaeological data and recent scholarship, the contributors offer a comprehensive view of Peter through analysis of both New Testament texts and later, noncanonical literature. Markus Bockmuehl concludes the volume by considering present-day questions about the role of Peter, popes, and church leadership
aus dem Vorwort: "The essys... are some of the highlights of a conference organized by Edinburgh University's Centre for the Study of Christian Origins in july 2013"
Hier auch später erschienene, unveränderte Nachdrucke
Includes indexes. - Includes bibliographical references and indexes
Keywords: Peter -- Peter -- 30 - 600; Peter -- the Apostle, Saint; Petrus -- Apostel, Heiliger; Konferenzschrift -- 2013 -- Edinburgh; Aufsatzsammlung; Frühchristentum; Rezeption; Petrus <Apostel, Heiliger>; Bibel / Neues Testament; Geschichtlichkeit